Scaffolding A Student's Development of Storytelling With Wordless Picture Books - Penny L. Beed; Ashley Shipp (Networks: An Online Journal for Teacher Research, 2005)
According to Kathryne Macgrath Speaker (2002), "Children involved in storytelling programs exhibit improved listening skills, better sequencing abilities, increased language appreciation and more thoughtful organization in their own writing." (p.184) As Speaker indicates, storytelling can be a very important tool for learning in the classroom. Storytelling is not only important in the classroom; it is also important to society. We all know that storytelling has been instrumental in the preservation of history for centuries. It is a means of sustaining cultural activities and beliefs. According to Seth Weaver Kahan, "Storytelling is one of the oldest and most powerful devices for building community" (Kahan, 2001, 26). I believe that storytelling can be used by students to make connections between home and school. Storytelling can help students learn about and build respect for classmates who are different from themselves. I think that if students were able to tell stories to their peers they would communicate a lot about themselves. This would be a good way for students to get to know each other and to build relationships. Students would learn how to construct and tell stories for an audience.